1996
DOI: 10.1159/000201377
|View full text |Cite
|
Sign up to set email alerts
|

Modification of Visceral Sensitivity and Pain in Irritable Bowel Syndrome by 5-HT<sub>3</sub> Antagonism (Ondansetron)

Abstract: Intrinsic neurons containing serotonin (5-HT) are involved in the regulation of gastrointestinal motor function and are also thought to be important in the modulation of visceral sensory function. We have evaluated the effect of a specific 5-HT3 antagonist (ondansetron, O) on visceral sensation and rectal compliance in a randomized, double-blind, cross-over, placebo (P) controlled study of·16 mg 3 times/day, in healthy volunteers and patients with irritable bowel syndrome (IBS). Symptoms were also evaluated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(60 citation statements)
references
References 19 publications
1
59
0
Order By: Relevance
“…Like in NUD patients, the benefit of 5-HT 3 receptor antagonists has not been evaluated in large clinical trials in patients with irritable bowel syndrome. The results of studies with small patient numbers are conflicting, but of course some reports show promising results [13, 25, 26]. …”
Section: Discussionmentioning
confidence: 99%
“…Like in NUD patients, the benefit of 5-HT 3 receptor antagonists has not been evaluated in large clinical trials in patients with irritable bowel syndrome. The results of studies with small patient numbers are conflicting, but of course some reports show promising results [13, 25, 26]. …”
Section: Discussionmentioning
confidence: 99%
“…A doubleblind pilot study with ondansetron (a 5-HT 3 -specific blocker) versus placebo in 14 patients with diarrhea-predominant IBS revealed no significant differences in terms of colonic transit modification between both groups, although there were 11 dropouts in this study [31]. Another double-blind study performed in 1996 with ondansetron versus placebo proved a significant decrease in abdominal distension and the frequency of abdominal pain compared with placebo [32]. Maxton et al [33] performed a similar placebo-controlled trial with ondansetron including 50 patients and demonstrated a significant reduction in the frequency of bowel movements and an increase in stool consistency in those with diarrhea-predominant IBS [33].…”
Section: Serotonin Antagonistsmentioning
confidence: 65%
“…Benefit was apparent for both agents, in patients of either sex. An old 5-HT 3 receptor antagonist widely used as an antiemetic, ondansetron, has showed benefits in patients with IBS in small trials [Steadman et al 1992;Goldberg et al 1996]. Recently, a large RCT of 120 patients with IBS-D showed that ondansetron of 4 mg for 5 weeks improves stool consistency, reduced urgency, frequency, and bloating, but does not reduce abdominal pain [Garsed et al 2014].…”
Section: Efficacy Of Ramosetron In Ibs-dmentioning
confidence: 99%